Relationship between Timed Up and Go performance and quantitative biomechanical measures of balance - Tendolkar, Prasad; Ibironke, Oluwaseun; Marchesi, Giorgia; De Luca, Alice; Squeri, Valentina; Nolan, Karen J.; Pilkar, Rakesh; Karunakaran, Kiran K. (Frontiers in Rehabilitation Sciences, 2024)
Traumatic brain injury (TBI) impairs sensory-motor functions, with debilitating consequences on postural control and balance, which persist during the chronic stages of recovery. Timed Up and Go (TUG) is a reliable, safe, time-efficient, and one of the most widely used clinical measures to assess gait, balance, and fall risk in TBI and is extensively used in inpatient and outpatient settings. Although TUG has been used extensively due to the ease of performing the test and excellent reliability, little research has been published that investigates the relationship between TUG performance and quantitative biomechanical measures of balance. The objective of this paper is to quantify the relationship between biomechanical variables of balance and the TUG scores in individuals with chronic TBI. Regression models were created with six biomechanical variables to predict TUG. The model with conservatively removed gait speed (i.e., TUG-1/GS) gave the best results with Root mean square error at ±2 seconds and explained over 69% of the variability.